Analysis and thought on quantum insert technology - Xue-bo ZHANG; Si WANG; Hong-xia ZOU (网络与信息安全学报)
Quantum insert (QI) is a technology that makes redirection attacks by injecting malicious content into certain sessions.A brief introduction of American “Quantum Insert” project was given and the connotation of this technology was discussed.It then looked into the application that quantum insert was put to in the Internet “Great Cannon” event.An open source QI tool made available by Fox IT,an IT security company,was then analyzed.An experimental verification environment was built using this tool and a verification was made.Finally,a thought was given on how to put QI to use in building network defense.